Analisis Efektivitas Cefazoline dan Ceftriaxone sebagai Antibiotik Profilaksis Bedah Sesar di RSIA Trisna Medika Tulungagung Periode Oktober–Desember 2021: Effectiveness Analysis of Cefazoline and Ceftriaxone as Cesarean Section Prophylactic Antibiotics at RSIA Trisna Medika Tulungagung Oktober-Desember 2021 - Nurisma Tria Harwiyanti; Dhanang Prawira Nugraha; Ana Amalia (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Cesareans antibiotic prophylaxis aims to prevent the clinical manifestations of SSI expected to occur. Theoretically, Cefazoline is considered more advantageous as a cesarean prophylactic antibiotic than Ceftriaxone. This study aims to compare the effectiveness of Cefazoline and Ceftriaxone as cesarean prophylactic antibiotics at RSIA Trisna Medika Tulungagung from October–December 2021. The study used a cross-sectional research design using 214 medical records data of patients with preoperative prophylactic antibiotics Cefazoline and Ceftriaxone (1:1). Data analysis includes antibiotic use profiles and therapeutic effectiveness data. Statistical analysis used the Mann-Whitney U Test. Research results showed that Cefazoline and Ceftriaxone have the same effectiveness as cesarean prophylactic antibiotics at RSIA Trisna Medika Tulungagung October – December 2021 based on pulse frequency, breath frequency, 10d post-op wound pain, purulent, dry wound, SSI, and LOS.